Towards Inclusive and Responsible Digital Innovations for Agri-food systems - Gakhar, Shalini; Patwar, Shelly; Singh, Kanika; Mehrotra, Nipun; Nagaraji, Satish (2023)
The ICTforAg+ India satellite event, hosted on December 19, 2023, at T-Hub in Hyderabad, was a convergence of professionals dedicated to advancing inclusive and responsible digital innovations in agri- food systems. Jointly organized by the Government of Telangana, CGIAR initiative on Digital Innovation (DI), and The Agri Collaboratory, the event offered a dynamic platform for 72 participants, including Agritech startups, NGOs, private and government sectors, and academia, to immerse in a vibrant local digital ecosystem and establish global connections. As an India-specific adjunct to the globally recognized ICTforAg series, the workshop celebrated its rich heritage of fostering digital solutions in agriculture since 2015. Characterized by its diverse attendance and an atmosphere charged with enthusiasm, the event marked a significant gathering of established and emerging leaders, spotlighting India's role in shaping digital agri-food systems.